Impact of the COVID-19 pandemic on tuberculosis laboratory services in Europe - Nikolayevskyy, Vladyslav (Eur Respir J, 2021)
Sustainable support from healthcare bodies is needed to preserve TB laboratory capacity, and maintain personnel and skills, to minimise negative effects of the COVID-19 pandemic on laboratory services severely disrupted in the early months of pandemic https://bit.ly/38camaL